Heavy metal (Pb, Ni, Cd) elimination from water and wastewater using an antibacterial modified cellulose filter paper as an efficient filtration membrane technology: A portable filtration with high selectivity - Milad Kazemnejadi (Results in Chemistry)
The study demonstrates that cellulose filter paper modified with covalently chelating ligands (FP@Si@SaPh) is highly effective in removing Ni, Pb, and Cd ions from aqueous environments. Optimal adsorption efficiency for these metals was achieved at pH 6–7 at room temperature, with the adsorption order being Pb > Cd > Ni. FP@Si@SaPh can be regenerated using an EDTA solution and reused without significant loss in adsorption efficiency. Isotherm analyses revealed that the adsorption of Ni and Cd conforms to both Freundlich and Langmuir models, while Pb adsorption aligns best with the Langmuir isotherm. Investigating the adsorption mechanism by high resolution XPS analyzes showed that the adsorption was done both through coordination with Schiff base ligands and through non-bonding electron pairs of N and O atoms on the surface of filter paper. Tests on shrinkage and swellability confirmed that the filter paper maintains its quality through multiple wetting and drying cycles, allowing for repeated use, wherein 0.9 mg/L and 0.4 cm changes in swellability and shrinkage was observed after five consecutive cycles. Additionally, the filter paper demonstrates high selectivity for Ni and is suitable for selective heavy metal adsorption. Its antibacterial properties against Escherichia Coli bacteria suggest potential application in household water purification systems, where it can remove heavy metals and inhibit bacterial growth.